Pengembangan Gim Point And Click Menggunakan Design, Play, Experience (DPE) Framework - Unggar Salsabila HSS; Wibisono Sukmo Wardhono; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Game with point and click genre is game where player interact with pointing location to virtual object in screen and then press button on device that use it. Point and click game that developed in personal computer have an advantage with acurate pointing device and large screen size. On smartphone android in other hand, user point some place in screen with their finger where accuracy is less. Screen size on smartphone is smaller than on personal computer so that resulting in object appear smaller. This becomes challenge to develop point and click game for smartphone android. The game is designed with DPE framework that divide design with several layer as follow: learning, storytelling, gameplay, user experience, and technology. Testing for this game is black box testing, usability testing, and fun testing. Black box testing is for testing the functionality of game that being developed. Usability testing is to determine is the purpose of the game already fulfilled. Fun testing is for find the fun factor of the game that being developed. From result of tests conducted, that all functionality is valid, the respondents are positives about the game, also there is three fun factors and three not fun factors.